A Brief Modified Family-Based Treatment Intervention for Youth With Mild Eating Disorders: A Case Series - Spettigue, Wendy; Aldaqqaq, Zizo; Isserlin, Leanna; Bishop, Brittany; Norris, Mark L.; Valois, Darcie; Obeid, Nicole (Frontiers in Psychiatry, 2020)
Background: Family-based treatment (FBT), an outpatient treatment which is typically offered for 6-12 months by specially trained therapists, is currently the first line treatment for adolescent anorexia nervosa and bulimia nervosa. The success of FBT for adolescents with moderate to severe eating disorders indicates a potential use for a short course of modified FBT which could be offered as an early intervention by non-specialized community mental health counselors to adolescents with mild or subsyndromal eating disorders. Methods: In 2016, 7 adolescents with mild eating disorders underwent treatment in the form of 5 FBT-inspired sessions (called ‘DREAMS’ sessions). The DREAMS sessions consisted of 5 replicable family sessions given over 6 weeks, each with a specific area of focus for treatment, such as nutrition and eating disorder symptoms, mood, relationships and anxiety. Charts of these 7 patients were reviewed in 2019 to determine whether this treatment might be worthy of further study. Results: Based on a review of the progress notes, all 7 patients reported an improvement in intake, a decrease in ED symptoms and an improvement in mood by the end of the sessions. All 7 families reported that the sessions had been beneficial. Conclusion: Early intervention is recommended for adolescents who present in the early stages of an eating disorder, yet there are no guidelines to recommend which treatment should be offered to this population. Further research is required to determine whether a short course of modified FBT, such as these 5 FBT-inspired ‘DREAMS’ sessions, may be an effective intervention to offer to youth who present with mild eating disorders.